Qualidade de sementes de feijão produzidas em sistema orgânico no oeste do Paraná - Gheller, Jardel Luiz (2008)
Brazil is currently the second largest producer of common bean (Phaseolus vulgaris) and most of its production comes from small properties. The productivity in these areas is small, and the technological level adopted. It is important that there is need for concern by farmers with quality seeds to be use, because it is one of the elements that guarantee the successful harvest. This study aimed to evaluate the quality of seeds of nine varieties of beans produced in the body system in two cities in the west of Paraná. The seeds were from two areas in Marechal Cândido Rondon and Sao Miguel do Iguaçu. The characters were assessed the degree of humidity (UM), examination of seeds infested (INF), mass of a thousand seeds (MMS), electrical conductivity (CND), first count of germination (PCG), germination test (VBG), ageing Accelerated (TEA), vigor and the viability of tetrazolium test (VITZ and VBTZ). The work supports the following conclusions: in Marechal Cândido Rondon, the cultivars Iapar 31 and Rosinha had the best average on tests of quality seed. The cultivar Iapar 31 was better on tests of: first count of germination (PCG), germination test (VBG), vigor and the viability of tetrazolium test (VITZ and VBTZ). The cultivar Rosinha showed better results for tests of: electrical conductivity (CND), first count of germination (PCG), germination test (VBG) and accelerated aging test (TEA). In São Miguel do Iguaçu, to cultivate Iapar 31 presented the best average on tests of: first count of germination (PCG), accelerated aging test (TEA) vigor and the viability of tetrazolium test (VITZ and VBTZ). Two cultivars (Rosinha and Carioca) had similar results on tests of accelerated aging (TEA), vigor and the viability of tetrazolium test (VITZ and VBTZ). It was found possible dormancy in seeds of both local